Premsa literària valenciana de postguerra: el cas de l'«Almanaque de Las Provincias» (1940-1951) - Cortés, Santi (Caplletra. Revista Internacional de Filologia, 2015)
The press played an important part in the literary developement during the post-war period, it was almost the only place where literary questions were discussed. This paper goes through those journals where the literary texts appeared during the fourties, especially the case of the Almanaque de Las Provincias.